Person-centered medical education: An opportunity to improve now more than ever - Parodi, José F. (2021)
How many times in your professional or academic practice have you said or heard the phrase "we care for people, not diseases"? However, how do you translate this into daily practice, what skills do you need, how did you learn them, how and where are they taught? You may also have heard: "I am the doctor and the one who knows what is good for you", "after God, you, my doctor" versus "the client is right" and "nothing about me, without me". Take a few seconds to reflect for a moment on the validity and relevance of each of these expressions in today's doctor-patient relationship.